A case of IgG4-related retroperitoneal fibrosis with multiple involvement - Zheng, Y-K.; Gu, N-Y.; Wu, J.; Fang, X.; Zhang, C.; Li, Q-Y. (Cellular and Molecular Biology, 2017)
To increase awareness of IgG4-related retroperitoneal fibrosis (IgG4-RRPF) and reduce clinical misdiagnosis. We report a 79-year-old man with multiple organs involvement of IgG4-RRPF, who developed right lower extremity edema, hemoptysis and fever. The abdomen computed tomography (CT) scan image showed lymph nodes enlargement. The positron emission tomography/CT scan image showed pancreatic malignancy with multiple nodal lymph node metastasis, lung fibroblast proliferation, and right lung apex bullae. The chest CT scan image showed pulmonary multiple lymph nodes with calcification in the mediastinum. Posterior peritoneum magnetic resonance imaging showed the body and tail of the pancreas parenchymatous mass. The serum IgG4 concentration was high. The fibrous connective tissue with IgG4-positive plasma cells infiltration in the left supraclavicular lymph node biopsy was found. Fiberoptic bronchoscopy showed diffuse alveolar hemorrhage, and the transbronchial lung biopsy found no cancer cells. The patient was treated with glucocorticoids and immunosuppressive agents. After 2 months treatment, the patient showed rapid improvement. This is a case of IgG4-RRPF with multiple organs involvement. Glucocorticoid is the first-line treatment.